The Role of Family in Fulfilling the Right to Education During the Covid-19 Pandemic: A Socio-Legal Approach - Atu Dewi, A.A. Istri Ari; Dwijayanthi, Putri Triari; Laksmi Dewi, Cokorde Istri Dian (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 2 (2021)DO - 10.24843/JMHU.2021.v10.i02.p03, 2021)
This paper aims to identify, analyze and elaborate on the role of the family in fulfilling the right to education during the Covid-19 pandemic as well as a model for family participation in fulfilling the right to education during the Covid-19 pandemic. This is a socio-legal research method or socio-legal research which examines the text and context with a statutory approach combined with the conditions in the community. The results show that online school is the best solution to guarantee the right to education as stipulated in Surat Edaran Nomor 15 of 2020 concerning Guidelines for Organizing Learning from Home in an Emergency for the Spread of Covid-19 and family role models in an effort to fulfill the right to education during the Covid-19 pandemic, which is in the form of awareness from parents or guardians to provide assistance during learning from home activities.